RETHINKING SELFIES: EMPOWERING THE MARGINALIZED THROUGH SELF-PORTRAITS - Nemer, David; Freeman, Guo Zhang (AoIR Selected Papers of Internet Research, 2015)
More than just a self-taken, static photo shared on social networking sites, selfies are considered nonverbal, visual communication that implies one’s thoughts, intentions, emotions, desires, and aesthetics captured by facial expressions, body language, and visual art elements. Previous studies have investigated selfies in light of adolescent development (e.g., how teenagers use selfies to seek attention; see McLean, 2014) and prestigious user groups (e.g., celebrities’ self-promotion; see Wallop, 2013). Although these studies generalize selfies as a relation between narcissism and public attention, between (re)construction of self-esteem and optimized (or selective) self-presentation, and between self-promotion and social capital, selfies are produced and experienced by people in sociocultural terms. It is difficult to understand selfies without taking into account the deeper sociocultural context in which they were created, used, and interpreted (e.g., in a non-Western culture). What happens, then, when selfies, as “fashionable” sociotechnical artifacts, are introduced to and adopted within user groups of sociocultural specificity, such as marginalized groups? We draw on a six-month ethnography performed by the first author, including user observations and 56 in-depth and semi-structured interviews in the favelas of Vitória, Brazil, to study slum residents’ selfie practices. The fieldwork focused on four Community Technology Centers (CTCs): two LAN houses (Life Games in Itararé and Guetto in Gurigica) and two Telecenters (one in Itararé and one in São Benedito). We used ethnography to emphasize how marginalized people experience and understand selfies, which puts them at the center of the research and posits that people themselves define their valued lives. We argue that practices of understanding, interpreting, and experiencing selfies are embedded in dense sociocultural contexts. For marginalized users who are suffering in a relatively severe living environment, selfies are not a shallow way to show narcissism, fashion, and self-promotion and seek attention; selfies, rather, empower the users to exercise free speech, practice self-reflection, express spiritual purity, improve literacy skills, and form strong interpersonal connections. This research contributes to a growing social scientific literature on selfies by rethinking selfies as empowerment and fostering a non-Western and nonconventional mode of knowing on people’s daily use of technology. This approach sheds light on the role of technology in various dimensions in people’s lives.